2011
DOI: 10.1007/978-3-642-20407-4_23
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of Functional Complexity as an Indicator of Overfitting in Genetic Programming

Abstract: Abstract.Recently, it has been stated that the complexity of a solution is a good indicator of the amount of overfitting it incurs. However, measuring the complexity of a program, in Genetic Programming, is not a trivial task. In this paper, we study the functional complexity and how it relates with overfitting on symbolic regression problems. We consider two measures of complexity, Slope-based Functional Complexity, inspired by the concept of curvature, and Regularity-based Functional Complexity based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…A complexity measure based on slope of line segments is proposed in [29]. The slope-based functional complexity (SFC) is computed by taking sum of differences of slope of consecutive line segments.…”
Section: ) Behavioral Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…A complexity measure based on slope of line segments is proposed in [29]. The slope-based functional complexity (SFC) is computed by taking sum of differences of slope of consecutive line segments.…”
Section: ) Behavioral Complexitymentioning
confidence: 99%
“…The slope-based functional complexity (SFC) is computed by taking sum of differences of slope of consecutive line segments. However, authors [29] calculated SFC measure for each problem dimensions separately in case of multi-dimensional problems. To overcome limitations of SFC, a new measure based on concept of measuring amount of variation in output is presented in [29].…”
Section: ) Behavioral Complexitymentioning
confidence: 99%
“…However, recent research has observed that overfitting can occur in absence of bloat [41,67]. Therefore, some researchers suggested that bloat and overfitting are two independent phenomena and should be tackled by separate mechanisms [67,217].…”
Section: List Of Publicationsmentioning
confidence: 99%
“…However, measuring the complexity of the candidate models is not a trivial task. A number of model complexity measures for GP have been proposed [42,217,224,233]. Some of them use the complexity of solutions as an indicator of overfitting, while others treat the complexity as an objective that needs to be optimised.…”
Section: List Of Publicationsmentioning
confidence: 99%
See 1 more Smart Citation